Hours worked and the US distribution of real annual earnings 1976–2019 - Fernández‐Val, Iván; van Vuuren, Aico; Vella, Francis; Peracchi, Franco (Journal of applied econometrics (Chichester, England), 2024)
Summary We examine the impact of annual hours worked on annual earnings by decomposing changes in the real annual earnings distribution into composition, structural, and hours effects. We do so via a nonseparable simultaneous model of hours, wages, and earnings. Using the Current Population Survey for the survey years 1976–2019, we find that changes in the female distribution of annual hours of work are important in explaining movements in inequality in female annual earnings. This captures the substantial changes in their employment behavior over this period. Movements in the male hours' distribution only affect the lower part of their earnings distribution and reflect the sensitivity of these workers' annual hours of work to cyclical factors.